Analisis Efisiensi Usahatani Ikan Nila pada Kelompok Nelayan Keramba Ulam Dewi Segara Tirta di Banjar Abang Desa Abangsongan Kintamani Bangli - NI WAYAN RUSTARINI; NI LUH PRIMA KEMALA DEWI; I DEWA AYU SRI YUDHARI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Analysis of The Efficiency of nile Tilapia Fish Farming in The Fishing Group of Keramba Ulam Dewi Segara Tirta in Banjar Abang Abangsongan Village Kintamani Bangli. Nile tilapia (Oreochromis Niloticus) is a type of freshwater fish that is widely cultivated in Indonesia, one of which is in Bali. Nile Tilapia has good growth so that many are cultivated in Bali, especially those conducted in this study, namely in the area of Lake Batur, Kintamani, Bangli. The purpose of the study was to identify the amount of income, efficiency, profitability and identify the profit sharing system reccepted by nile tilapia farmers in the Fishing Group Keramba Ulam Dewi Segara Tirta. The data analysis method used is quantitative data and data collection is done by census technique involving 12 respondents. The data used is primary and secondary data. The results showed the acceptance of the Fishing Group Keramba Ulam Dewi Segara Tirta amounted to Rp209.100.000 with a total cost of Rp63.285.499 and the income of the keramba group of Rp145.814.501 R/ C Ratio has a value of 3.30 which means the farmer experienced a profit and profitability value of 230% which shows nile tilapia farming is worth developing. While the profit sharing system that is evenly distributed from 80% of the income earned by individual farmers amounted to Rp9.720.966, plus the wages of group farmers' workers paid at the end of the production period amounted to Rp560.625. The total income received by individual farmers amounted to Rp10.281.591 in one production process of 6 to 7 months.